Oxidative stress and protein damage responses mediate artemisinin resistance in malaria parasites - Rocamora, Frances (2018)
Due to their remarkable parasitocidal activity, artemisinins represent the key components of first-line therapies against Plasmodium falciparum malaria. However, the decline in efficacy of artemisinin-based drugs jeopardizes global efforts to control and ultimately eradicate the disease. To better understand the resistance phenotype, artemisinin-resistant parasite lines were derived from two clones of the 3D7 strain of P. falciparum using a selection regimen that mimics how parasites interact with the drug within patients. This long term in vitro selection induced profound stage-specific resistance to artemisinin and its relative compounds. Chemosensitivity and transcriptional profiling of artemisinin-resistant parasites indicate that enhanced adaptive responses against oxidative stress and protein damage are associated with decreased artemisinin susceptibility. This corroborates our previous findings implicating these cellular functions in artemisinin resistance in natural infections. Genomic characterization of the two derived parasite lines revealed a spectrum of sequence and copy number polymorphisms that could play a role in regulating artemisinin response, but did not include mutations in pfk13, the main marker of artemisinin resistance in Southeast Asia. Taken together, here we present a functional in vitro model of artemisinin resistance that is underlined by a new set of genetic polymorphisms as potential genetic markers.